A simple low-molecular-mass organic gelator based on salicylaldehyde acylhydrazone: Gelation behavior and selective fluorescence sensing of Y3+. (December 2021) - Zang, Libin; Luan, Changhui; Tang, Xiaodan; Lu, Jilong; Zhao, Yuyan
Abstract: A simple low-molecular-mass organic gelator based on salicylaldehyde acylhydrazone had been synthesized and carefully studied. This gelator could form a thermo-reversible supramolecular organogel in many solvents by self-assembling them into nanofibers. Notably, it could even solidify crude oil floating on seawater. Moreover, the gelator was triggered to form a yellow metallogel with blue-green fluorescence by adding Y 3+ . In addition, it could act as an efficient fluorescent probe for the selective sensing of Y 3+ in the solution containing water. The detection limit of Y 3+ was 1.039 μM. Furthermore, test strips containing this compound were prepared, successfully used for on-site monitoring of Y 3+ in water. Graphical abstract: Image 1 Highlights: A simple gelator based on salicylaldehyde acylhydrazone has been developed. The compound exhibits excellent gel properties, including solidifying crude oil. The compound can act as a highly selective fluorescent probe for Y 3+ . The test strip containing the compound can detect Y 3+ in water.